ANALISIS POTENSI PERTANIAN DAN PERKEBUNAN SEBAGAI SUMBER DAYA ALAM UNGGULAN DI DESA TANGLAPUI - Novi Greace Makena; Jennie Hapliani Tunliu; Mita Lodia Sing; Paulina Arokoil; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This study aims to analyze the potential of agriculture and plantations as a leading natural resource in Tanglapui Village, East Alor District, Alor Regency. The study used a qualitative approach through field observations and interviews with the Tanglapui Village Head as the primary informant. The results indicate that the agricultural sector is the village's leading potential, with approximately 600 hectares of rice paddies. Rice productivity is quite high, especially during the rainy season when irrigation is adequate. The use of urea, considered the most effective primary fertilizer, and NPK fertilizer to support fertility, also contributes to increased yields. Agricultural management in this village is also strengthened by 14 farmer groups that play a role in organizing planting activities, managing land, and improving farmer capacity. In the plantation sector, the community cultivates various commodities such as candlenut, turmeric, cashew, corn, porang (porang) sweet potato, cassava, and bananas on approximately 20 hectares of land. The soil characteristics in Tanglapui Village include black soil, red soil, and clay. Black soil is the most fertile type, while red soil and clay have lower fertility levels. However, some crops, such as candlenut and cashew, are more suited to growing in red soil, thus still providing economic benefits to the community. This demonstrates the variation in crop suitability based on soil conditions. Overall, the agricultural and plantation potential in Tanglapui Village offers excellent development prospects, with the rice field sector being the most prominent. Future development can be achieved through improving irrigation systems, sustainable fertilizer use, strengthening farmer groups, and adapting cropping patterns based on soil characteristics. This research provides a comprehensive overview of the village's natural resource strengths as a foundation for sustainable development.